USE OF E-COMMERCE SALES IN FASHION PRODUCT HOMEPAGE FOR ELLE - Mudiyanti Mudiyanti; Fitri Sjafrina Ir. MMSI (Jurnal Sistem Informasi, 2001)
E-Commerce initially limited to the sale of electronic goods such as compact disk (CD) and reading books in Indonesian and in English, but are now starting to spread to food products to medicines and even fashion. With so many things that have been presented on the internet facilities, so the writer took the research field of fashion as much attention from the public in accordance with the time. Product Elle is a fashion business who opened his shop on the Internet through ECommerce. in this problem the authors tried to create a Homepage in dealing with marketing via the E-Commerce. Here the author uses the hypertext transfer protocol (HTTP) and Uniform Resource Locator (URL) as the foundation of the theory. After analyzing the fashion was in desperate need in the development of the fashion world one of Elle product. Elle current products already widely known to the public since opening his shop on the Internet through E-Commerce. The making of this homepage is an alternative solution that is used so that the entrepreneur can provide the best service for consumers.